Exploring Recent Trends in Youth Justice Reconvictions: A Challenge to the Complexity Thesis. (December 2020) - Bateman, Tim; Wigzell, Alexandra
In recent years, it has become accepted wisdom that children subject to youth justice intervention, in England and Wales, are more complex than previously, as a consequence of a substantial rise in diversion from the system that filters out children with lower levels of need and less entrenched offending. This 'complexity' thesis has been used to explain rises in rates of reoffending. This article demonstrates that the patterns shown in the reoffending data are not those that would be predicted by the complexity thesis. Indeed the data suggest that some groups of children may be less entrenched in offending than hitherto.